Optical and dielectric relaxor behaviour of Ba(Zr0.25Ti0.75)O-3 ceramic explained by means of distorted clusters - Badapanda, T.; Rout, S. K.; Cavalcante, L. S.; Sczancoski, J. C.; Panigrahi, S.; Longo, Elson [UNESP]; Li, M. Siu (Iop Publishing Ltd, 2009)
In this work, Ba(Zr0.25Ti0.75)O-3 ceramic was prepared by solid-state reaction. This material was characterized by x-ray diffraction and Fourier transform Raman spectroscopy. The temperature dependent dielectric properties were investigated in the frequency range from 1 kHz to 1 MHz. The dielectric measurements indicated a diffuse phase transition. The broadening of the dielectric permittivity in the frequency range as well as its shifting at higher temperatures indicated a relaxor-like behaviour for this material. The diffusivity and the relaxation strength were estimated using the modified Curie-Weiss law. The optical properties were analysed by ultraviolet-visible (UV-vis) absorption spectroscopy and photoluminescence (PL) measurements at room temperature. The UV-vis spectrum indicated that the Ba(Zr0.25Ti0.75)O-3 ceramic has an optical band gap of 2.98 eV. A blue PL emission was observed for this compound when excited with 350 nm wavelength. The polarity as well as the PL property of this material was attributed to the presence of polar [TiO6] distorted clusters into a globally cubic matrix.